Analisis Pendapatan Usaha Rumah Tangga Kacang Aspal di Desa Loli Oge Kabupaten Donggala - Alda Sela Sasmita Iyono; Rita Suirlan; Laendatu Paembonan; Andi Herman Jaya; Nurnaningsih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the income of asphalt bean household businesses in Loli Oge Village, Donggala Regency. This research uses qualitative research using primary and secondary data. Data collection was carried out through observation, interviews and questionnaires. The data analysis used is descriptive , namely calculating revenue, production costs and business income. The results of income analysis calculations show that the Asphalt Nut household business is very profitable because the income received by the owner for one month is IDR . 2,696,333,- per month, received revenue of IDR. 6,000,000,- per month minus production costs of IDR. 3,303,667,-. Keywords: Home Industry, Revenue, Costs, Income